(untitled) (Current Horticulture, 2024)
During the 2016 summer season, a study was conducted at the Department of Horticulture, Bihar Agricultural University, Sabour, Bhagalpur, to evaluate 26 marigold (Tagetes species) genotypes, including 23 experimental lines and three controls. The experiment followed a randomized complete block design with three replications. The results of the analysis of variance revealed highly significant differences (p<0.05) among the genotypes for various growth, flowering, and yield-related traits. Among the genotypes, BRMG 113 exhibited the best performance in terms of the number of flowers per plant (394.98), duration of flowering (76.80 days), flower yield (39.98 kg per plot), and overall yield (53.31 tonnes per hectare). The genotype Super red showed the minimum number of days for the appearance of the first flower (48.20 days) and 50% flowering (65.73 days). On the other hand, BRMG 113 had the maximum flowering duration (76.80 days), number of flowers per plant (394.98), and flower yield (1599.21 g per plant). The genotype MDU 1 recorded the significantly highest number of days for the appearance of the first flower (95.73 days), while Pusa Arpita had the shortest flowering duration (29.07 days). These findings indicate that the genotype BRMG 113 shows promising characteristics for the summer season, particularly in terms of flower yield and duration of flowering. Super red also exhibited early flowering, which may be desirable in certain contexts. Further studies can be conducted to explore the potential of these genotypes in different environmental conditions and evaluate their suitability for commercial cultivation.